2023
DOI: 10.1111/epi.17501
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the cross‐cultural applicability of a harmonized approach to cognitive diagnostics in epilepsy: Initial results of the International Classification of Cognitive Disorders in Epilepsy in a Spanish‐speaking sample

Abstract: Objective This study was undertaken to evaluate the cross‐cultural application of the International Classification of Cognitive Disorders in Epilepsy (IC‐CoDE) to a cohort of Spanish‐speaking patients with temporal lobe epilepsy (TLE) living in the United States. Methods Eighty‐four Spanish‐speaking patients with TLE completed neuropsychological measures of memory, language, executive function, visuospatial functioning, and attention/processing speed as part of the Neuropsychological Screening Battery for Hisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Our study presents one of the first expertly curated German cohorts with cognitive phenotyping that underwent a broad battery of neuropsychological tests spanning 5 cognitive domains. Cognitive phenotyping has previously been established in a large American English‐speaking cohort, 4 and recently validated in an American Spanish‐speaking cohort 37 . Our study shows broader applicability of the IC‐CoDE criteria approach and thus aids in the undertaking to standardize cognitive research across countries and languages.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our study presents one of the first expertly curated German cohorts with cognitive phenotyping that underwent a broad battery of neuropsychological tests spanning 5 cognitive domains. Cognitive phenotyping has previously been established in a large American English‐speaking cohort, 4 and recently validated in an American Spanish‐speaking cohort 37 . Our study shows broader applicability of the IC‐CoDE criteria approach and thus aids in the undertaking to standardize cognitive research across countries and languages.…”
Section: Discussionmentioning
confidence: 63%
“…Cognitive phenotyping has previously been established in a large American Englishspeaking cohort, 4 and recently validated in an American Spanish-speaking cohort. 37 Our study shows broader applicability of the IC-CoDE criteria approach and thus aids in the undertaking to standardize cognitive research across countries and languages. In our cohort, the largest group of patients was categorized into the MDI (53.2%), followed by FI (29.8%), and finally MI (16.9%) cognitive groups.…”
Section: Discussionmentioning
confidence: 70%
“…In fact, in a sample of 1,409 young-tomiddle aged adults with temporal lobe epilepsy, 49% of the patients with a Single Domain phenotype had isolated deficits in language (53). In a sample of Spanish-speaking patients with temporal lobe epilepsy, memory was the most commonly impaired domain within the Single Domain phenotype (55). The differences in the nature of the Single Domain phenotype across studies may be due to varying underlying epilepsy etiologies, epilepsy-related clinical factors, sociodemographic characteristics, or differences in brain abnormalities (e.g., lateral versus mesial temporal lobe involvement).…”
Section: Cognitive Phenotypes In Loementioning
confidence: 99%
“…Our group has shown that in young-to-middle aged adults, the phenotyping approach better captures the heterogeneity inherent both within and across epilepsy syndromes compared to analyzing individual scores in isolation (40, [49][50][51][52][53][54][55]. We have demonstrated that cognitive phenotypes are stable and robust across cohorts and are associated with distinct patterns of brain imaging abnormalities (49,51,56,57).…”
Section: Introductionmentioning
confidence: 99%
“…5 Of interest, a recent large-scale, multicenter study demonstrated significant heterogeneity in IC-CoDE phenotypes in adults with TLE (i.e., 50% intact, 26% single-domain, 14% bi-domain, 10% generalized), 5 which has since been replicated in independent cohorts. 12,13 Although it remains unclear what combination of factors account for the variability in cognitive phenotypes in adults with TLE, the initial IC-CoDE proposal suggested several potential modifiers as part of the new taxonomy (i.e., extent of impairment, etiology, mood), which have yet to be studied in clinical samples. 5 The goal of the current study was to investigate the relationship between psychiatric comorbidities and IC-CoDE phenotypes in a large cohort of adults with TLE.…”
Section: Introductionmentioning
confidence: 99%